sinA+tanA/1-cosA=1+secA
Attachments:
![](https://hi-static.z-dn.net/files/d11/1361335bdfa3012e1eb2e3148ad91e95.jpg)
Answers
Answered by
5
here is ur answer...first attachment is d answer of ques written by you n second attachment is d answer of ques given in d picture.
Attachments:
![](https://hi-static.z-dn.net/files/d87/ff08a9071c4a97e20f1d3dfff4d854c8.jpg)
![](https://hi-static.z-dn.net/files/ded/4d2e0c3afd03dd081e9cc65efda5ddf0.jpg)
aryan6698:
what should i do to let you know the problems personally
Answered by
1
Answer:
given that sec a -1/ sec a +1 =1-cos a/ 1+ cos a
to prove LHS=RHS
now, sec a = 1/ cos a
so, (1/cos a-1) / (1/cos a+ 1)
==( 1-cos a/ cos a) / (1+cos a /cos a)
== 1-cos a / 1+cos a = RHS
Step-by-step explanation:
Similar questions